Catalytic applications of aerogels - Choi, Jinsoon; Suh, Dong Jin (SPRINGER/PLENUM PUBLISHERS, 2007)
This paper is a review of studies on aerogel synthesis and its application for catalytic uses, which have been conducted for the past decade at the Clean Technology Research Center, Korea Institute of Science and Technology. Various organic and inorganic aerogels employing sol-gel modifications exhibited catalytically favorable textural and chemical properties such as extremely high porosity, high surface area, well-developed mesoporosity, good thermal stability, and high dispersion, which eventually led to excellent performance in catalytic reactions. Reactions observed in these studies include hydrogenation, photodecomposition, selective oxidation, complete oxidation, ammoxidation, reforming, and electrooxidation. The specific catalytic behaviors can be explained in terms of the strong active sites-support interactions, high thermal stability, and extremely high dispersion.
Keywords: METAL-OXIDE AEROGELS; SOL-GEL SYNTHESIS; COMPOSITE AEROGELS; CARBON-MONOXIDE; OXIDATION; TEXTURE; SIZE; GAS